Analisis Dampak Budaya Organisasi dan Kompetensi dalam Meningkatkan Kinerja Pegawai DISDIK Jawa Barat - Sholihannisa, Lulu Ulfa (Program Studi Administrasi Bisnis, 2024)
This research aims to analyze the impact of organizational culture and competence on employee performance at the West Java Ministry of Education, both simultaneously and partially. The method used is a descriptive-verificative method, with the population being the employees at the West Java Ministry of Education and a sample of 50 people, in addition to using primary data. This research yields an average interpretation of the organizational culture variable at 3.75%, the competence variable at 3.75%, and the employee performance variable at 3.82%. The analysis using path analysis shows that there is a positive and highly significant influence of organizational culture and competence on employee performance at the West Java Ministry of Education, both partially and simultaneously, amounting to 60.8%.